Historians and the Historical Policy - Stobiecki, Rafał (Dějiny – teorie – kritika, 2007)
The main aims of the article are, first, to present the main issues of the recent Polish debate about the historical policy, second, to reconstruct the most important arguments in the discussion and, third, to answer the question of what this debate is saying about historians themselves. The study portrays the dispute over the very notion of ‘historical policy’ and the different perspectives on how such policy, if ever, should function. Further, it analyses how the lines of division between various groups of historians and politicians in contemporary Poland are strengthened by generational differences, political preferences and, last but not least, by different images of the historian and his social role in today’s society. The author points to the importance of the societal and political context, in particular the compelling question of how the Polish patriotism at the beginning of the 21st century should be shaped and what role history or historical policy should play in it. The study concludes with considerations on the merging of history and memory in recent years and its far-reaching consequences for both, the history as political and commercial tool as well as the historian, his social and academic position.